Vascular Surgery - Lumley, J.S.P; Hoballah, Jamal J. (Springer Surgery Atlas Series,, 2009)
The aim of the Springer Surgery Atlas Series is to a provide step-by-step guide for surgeons undertaking the commom operations in each specialty. The experienced editors of the Vascular Surgery volume have selected the procedures that currently make up their speciality and have invited a team of experts to contribute to these areas. The authors present a detailed practical guide for each procedure; their instructions are complemented by full color clear uncomplicated diagrams. The reader is thus provided with the means of undertaking safe reflective skilled surgery, this being the basis for a successful outcome.